LED Based Spectrophotometer can compete with conventional one - Mohammad, Karim Aly; Zekry, Abdelhalim; Abouelatta, Mohamed (International Journal of Engineering and Technology, 2015)
Spectrophotometers are the common devise used for blood analysis. These analyses are simply optioned from the transmittance of monochromatic light through a blood sample. It disperses their light sources by different techniques; the simplest one is the use of interference filters in front of broad-band light source. As Interference bandpass filters are relatively inexpensive wavelength selectors. Interference filters that allow transmission of a predetermined wavelength while rejecting or blocking other wavelengths are widely used in instrumentation for clinical chemistry. On the other hand, the lights emitting diodes (LEDs) emits a specified band and have a wide selection options.Â  An economic device based on LEDs (LED based spectrometer) is explained in this work. Instead of the wide spectrum light source and filters (commercial spectrophotometer), The LED based spectrophotometer is calibrated with standard solutions, and its measurement results is compared with the Mindray BS-200 Chemistry Analyzer (commercial spectrophotometer). The comparison shows acceptable results between both spectrophotometers with maximum error 2.33%. The errors can be reduced by applying more fining alignment. Another benefit of the new designee is to minimize testing costs.